2017
DOI: 10.1039/c7cp03835f
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic CVD synthesis of boron nitride and carbon nanomaterials – synergies between experiment and theory

Abstract: Low-dimensional carbon and boron nitride nanomaterials - hexagonal boron nitride, graphene, boron nitride nanotubes and carbon nanotubes - remain at the forefront of advanced materials research. Catalytic chemical vapour deposition has become an invaluable technique for reliably and cost-effectively synthesising these materials. In this review, we will emphasise how a synergy between experimental and theoretical methods has enhanced the understanding and optimisation of this synthetic technique. This review ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 532 publications
2
29
0
Order By: Relevance
“…Despite the close structural relationship with carbon nanostructures, the factors governing the synthesis and production of BNNSs are different from their carbon analogues, 8 , 9 owing to the B–N chemistry that involves both ionic and covalent bonding, and the need for B–N element alternation in any thermodynamically stable BN structure. BNNTs, which are harder to synthesize than carbon nanotubes (CNTs), 10 have been grown by arc discharge, 11 laser ablation, 12 substitution reactions from CNTs, 13 ball-milling, 14 chemical vapor deposition (CVD), 11 boron oxide CVD (BOCVD)/floating zone method, 15 and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the close structural relationship with carbon nanostructures, the factors governing the synthesis and production of BNNSs are different from their carbon analogues, 8 , 9 owing to the B–N chemistry that involves both ionic and covalent bonding, and the need for B–N element alternation in any thermodynamically stable BN structure. BNNTs, which are harder to synthesize than carbon nanotubes (CNTs), 10 have been grown by arc discharge, 11 laser ablation, 12 substitution reactions from CNTs, 13 ball-milling, 14 chemical vapor deposition (CVD), 11 boron oxide CVD (BOCVD)/floating zone method, 15 and others.…”
Section: Introductionmentioning
confidence: 99%
“… 25 It is hypothesized in the literature that hydrogen in nitrogen plasma is necessary to prevent the recombination of nitrogen atoms to non-reactive dinitrogen molecules. 8 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…Besides CNT hybrid systems with polymers, spinning macroscopic yarns out of different CNT starting materials like sheets and arrays is a promising way to incorporate these properties into practical materials. These carbon nanotube yarns (CNY) have a high tensile strength [6], are extremely flexible and very light weight, which makes these materials promising candidates for electrical wiring in different applications [7][8][9][10][11]. However the physical properties, especially the electrical conductivity, still lag behind individual CNT and copper [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been employed in the synthesis of N-CNTs; namely arc-discharge [24], laser deposition [25] and chemical vapour deposition (CVD) [26]. Of these, the CVD technique has been the method commonly used for large-scale N-CNT synthesis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sakurai et al [37] reported that the introduction of the oxygencontaining molecule (e.g. H 2 O) during CVD synthesis enhanced the growth of CNTs and prolong catalyst lifetime at temperatures above 750 • C. This resulted in the removal of amorphous carbon through water vapour etching to give a graphitic nanostructured carbon network [26]. Fatuba et al [38] also reported that the addition of oxygen-containing aromatic compounds (i.e.…”
Section: Introductionmentioning
confidence: 99%